Two new Haploops species (Crustacea: Gammaridea: Ampeliscidae) from the North Atlantic Ocean: H. bjarnii and H. quebecoisis [Contribution to the knowledge of the Haploops genus. 9.] - Bellan-Santini, D.; Kaim-Malka, R.a.; Dauvin, J.c. (Zootaxa, 2018)
Two new Haploops species are described, both from the North Atlantic Ocean: Haploops bjarnii nov. sp. from around the Faeroe Islands and Iceland, and Haploops quebecoisis nov. sp. from the Saint Lawrence Gulf, off Canada. Haploops bjarnii is a species morphologically close to H. islandica Kaim-Malka, Bellan-Santini & Dauvin, 2016. These are two blind Haploops species, with long antennae. Haploops quebecoisis is morphologically similar to H. sibirica Gurjanova 1929, both species having 2 pairs of corneal lenses in the same position. A table of the 75 morphological characters is presented that can be used permitting to distinguish the new species from similar species.